A low cost alternative for analyzing ergonomic activity: measurement and registration of upper member movement (MMSS) - Sales de Oliveira, Altemar; Sá Menezes da Motta, Rosa Amelita; Bárbara de Oliveira, Saulo; Gomes Cunha, Gerson (Revista Gestão da Produção Operações e Sistemas, 2008)
This article presents the partial result of a study that aims at proposing an alternative, low cost solution for measuring and registering the angles of articulations formed by humans upper members during execution of a workers activities. That measurement and those registrations are made at the moment of observation of a work activity by an ergonomics professional. The methodology included bibliographical review; selection of computer tools to be used; construction of the prototype for the solution, using virtual reality techniques; application of the solution; and elaboration of final considerations, starting with informal interviews. The proposal in question has a considerably lower cost in comparison with traditional methods and it needs to be extended to meet to the needs of observation of activities at workstations. Key words: Analysis of Ergonomic Activity; Ergonomics; Upper Members; Computational Vision; Increased Reality; Virtual Reality.